O uso de pseudopotenciais e modelos HF/MP2/DFT na previsão de freqüências vibracionais em complexos metálicos - Giannerini,Tiago (2004)
Four different pseudopotentials and three methodologies were employed in the calculation of the geometry and the frequencies of metal complexes like [M(NH3)2X2] [X=halogen, M=Zn, Cd], and [Hg(NH3)2]Cl2. The vibrational assignments were carefully checked and compared to the theoretically calculated ones. Graphical procedures were employed to estimate family errors and their average behavior. The calculated results show the SBK-X basis set with the best results for the geometries and calculated frequencies, for individual species and statistical results. Its use is recommend, mainly if the neighborhood atoms are described with similar pseudopotentials. Excellent results were also obtained with the Hay and Wadt pseudopotential.